CIRCULATING PROTEINS AS DIAGNOSTIC BIOMARKERS IN BREAST CANCER - Dinh Thi Thao,; Nguyen Cam Thach,; Vu Van Tuyen,; Tran Quang Huy,; Nguyen Thi Anh Tuyet,; Nguyen Van Tuyen,; Tran Thai Ha, (Tạp chí Y học Quân sự, 2024)
Purpose: Summary of tumor-produced circulating proteins as biomarkers in breast cancer (BC) detection. Subjects and method: A meta-analysis of 50 researches on protein biomarkers in BC diagnosis. Results: Many studies have shown that tumors continuously release components such as protein, RNA, and DNA into the bloodstream during apotosis. There are different protein markers, as tissue markers and serum markers involved assisting diagnosis, but none of them can independently establish the final diagnotic BC at an early stage. Therefore, scientific communities have been putting lots of effort to discover biomarkers for better identifying this malignant disease at earlier stages.